A global perspective on carotenoids: Metabolism, biotechnology, and benefits for nutrition and health. (April 2018) - Rodriguez-Concepcion, Manuel; Avalos, Javier; Bonet, M. Luisa; Boronat, Albert; Gomez-Gomez, Lourdes; Hornero-Mendez, Damaso; Limon, M. Carmen; Meléndez-Martínez, Antonio J.; Olmedilla-Alonso, Begoña; Palou, Andreu; Ribot, Joan; Rodrigo, Maria J.; et al.
Abstract: Carotenoids are lipophilic isoprenoid compounds synthesized by all photosynthetic organisms and some non-photosynthetic prokaryotes and fungi. With some notable exceptions, animals (including humans) do not produce carotenoids de novo but take them in their diets. In photosynthetic systems carotenoids are essential for photoprotection against excess light and contribute to light harvesting, but perhaps they are best known for their properties as natural pigments in the yellow to red range. Carotenoids can be associated to fatty acids, sugars, proteins, or other compounds that can change their physical and chemical properties and influence their biological roles. Furthermore, oxidative cleavage of carotenoids produces smaller molecules such as apocarotenoids, some of which are important pigments and volatile (aroma) compounds. Enzymatic breakage of carotenoids can also produce biologically active molecules in both plants (hormones, retrograde signals) and animals (retinoids). Both carotenoids and their enzymatic cleavage products are associated with other processes positively impacting human health. Carotenoids are widely used in the industry as food ingredients, feed additives, and supplements. This review, contributed by scientists of complementary disciplines related to carotenoid research, covers recent advances and provides a perspective on future directions on the subjects of carotenoid metabolism, biotechnology, and nutritional and health benefits.